Assessment of Vaccination Rates among Smokers and Non-Smokers at a Student-Run Free Clinic - Carissa Harnish-Cruz; Jeremy Silver; Susan Veldheer; Seong Ho Jeong; Alexis Reedy-Cooper (Journal of Student-Run Clinics, 2021)
Background: While student-run free clinics (SRFCs) increasingly serve as part of the safety net for the uninsured and underinsured, it is unknown whether SRFCs consistently follow immunization guidelines in patients that smoke. This study characterized the preventative care in our clinic by evaluating the rate of adult immunizations and referrals of patients that smoke to cessation treatment.Methods: We conducted a retrospective chart review of patients seen in 2016 at the LionCare Free Clinic. Data extracted included tobacco smoking status, desire to quit, smoking cessation treatment referrals, influenza and pneumococcal vaccination status, and demographics. Chi-square tests and Fisher Exact analysis were used to examine differences in influenza and pneumococcal vaccination rates in smokers versus non-smokers. We assessed the rate of interested smokers who received a referral to cessation therapy.Results: In 2016, 498 patients were evaluated, of whom 67% were smokers. Among smokers, 21% reported receiving the influenza vaccination compared to 20% of non-smokers (p=0.85). Seven percent of patients who smoke received the pneumococcal vaccine compared to 5% of non-smokers. Of the total patients who were vaccinated, a small percentage received the vaccines in the clinic. Although 66% of smokers reported interest in quitting during the first clinic visit, only 3% were referred to a smoking cessation program.Conclusion: SRFCs face challenges in providing preventative health care for the underserved population. Despite guidelines recommending smokers receive the pneumococcal vaccine before age 65, few patients received it. Quality improvement interventions are needed to improve preventative health services to this vulnerable population.